Entangled ecosystems: the impact of macroplastic litter on Mytilus galloprovincialis communities in northwestern Spain - Jacob Houvener; Ignacio Moreu; Eva Cacabelos; Ignacio Gestoso; Jose M. F. Babarro; Mark Lenz (Frontiers in Marine Science, 2025)
Plastic litter in the ocean has gained significant attention over recent decades, with much of the focus on microplastics. However, macroplastic litter is prevalent in marine environments, and while its effects on single organisms is well documented, its effects on community-level biological structures remain poorly understood. This study investigates the impact of macroplastic litter—specifically polyethylene film (shopping bags) and nylon filament (fishing line)—on Mytilus galloprovincialis aggregates and their associated fauna in the Ría de Vigo, NW Spain. Using a fully factorial experimental design, 30-mussel aggregates were assembled incorporating plastic litter in different abundances and were deployed in situ for 4 weeks. After this time, physiological responses (respiration and filtration), structural complexity (rugosity index), particulate matter retention, body condition index (BCI), and associated mobile faunal diversity were measured. Mussels in the High/Filament treatment showed an 18% lower respiration rate and a 65% reduction in filtration capacity compared to controls, while the Low/Filament treatment reduced filtration by 40%. No significant effects were found on BCI, particulate retention as well as on the diversity and composition of the associated macrofauna. Interestingly, aggregates with low plastic content exhibited a slightly higher structural complexity than those with high amounts of plastic. This study highlights that macroplastics can subtly alter the functionality of mussel beds without dramatically affecting the diversity of the associated fauna. These insights underscore the need to assess physical interactions of organisms with plastic litter also at the community level.